Fecundity and egg size in bigeye scad (Selar crumenophthalmus Bloch) from Tanon Strait. - Perez, Ruby Mae T.
The reproductive biology of bigeye scad Selar crumenophthalmus was investigated through evaluation on its fecundity and egg size. Bigeye scad were sampled from May to July, 2016 in Ayungon and Bindoy, Negros Oriental. Batch and total fecundity of the species were determined using gravimetric method. Egg sizes were measured using ImageJ public domain software. Fecundity estimates and egg sizes were correlated with female fish size using simple linear regression and ANOVA. Results showed that total fecundity significantly increases with fish length and weight (gonad and body). However, batch fecundity cannot be well predicted with fish size that may be due to certain environmental factors and biological aspects if the species. Egg size is significantly correlated with batch fecundity but independent to fish length as a consequence of the species batch spawning strategy and environmental conditions. The data provided in the study addresses the optimization of recruitment and sustainability of the species.